(untitled) (Revista Brasileira de Plantas Medicinais, 1999)
A general procedure was developed for the simultaneous separation of flavonoids and naphthopyrones from the polar extracts of the capitula from Brazilian everlasting plants is described. The ethanolic extracts of several species from the Paepalanthus genus (Enocaulaceae) were fractionated by droplet countercurrent chromatography followed by column chromatography on pvp and sephadex LH-20. The isolated compounds were identified by spectrometric analysis and comparison with literature data. This approach led to the isolation of 9-O-β-D-giucopyranosylpaepalantine (1), 9-O-β-D-glucopyranosyl(1 —>6)allopyranosylpaepalantine (2). along with the flavonoids 6-methoxykaempferol (3). 3-O-β-D- glucopyranosyl-6-methoxykaempferol 4), paluletin (5). 3-O-β-D-rutinosylpatuletin (6), 7-O-β-D- glucopyranosylquercelagetin (7), 5,7,4’-trihydroxy’6,3’dimethoxyflavone (8) and 5,7,4’-trihydroxy-6,3’- dimethoxyflavonol (9).